Sistem Penunjang Keputusan Penilaian Kinerja Karyawan Berprestasi Menggunakan Acuan MBO dan Metode AHP Menggunakan Aplikasi Expert Choice - Rudi Sutomo; Johny Hizkia Siringo Ringo (Ultimatics : Jurnal Teknik Informatika, 2018)
In the determination of employees who have the achievement required assessment of the assessment. There are several policy setting criteria to be able to prevent subjective decision-makers such as the influence of "likes and dislikes", so it is often wrong to judge employees. This paper is intended to provide a solution to the problem of choosing qualified and qualified employees using the AHP method and using decision support systems application Expert Choice to assist decision making in determining outstanding employees based on MBO method references. From the result of comparison of criteria weight that has been inputted and has been adjusted with comparison matrix Sub Criteria of Achievement then got that occupy the highest priority data that is consumer satisfaction with point 0,434, discipline with point 0,285, operational performance with point 0,071 and achievement with point 0,058 with inconsistency 0, 03 with 0 missing judgments. The results of AHP calculations will be applied to produce the highest intensity of employee priority outputs so that employees with the highest score are eligible for rewards or rewards. Index Terms—AHP, Aplikasi Expert Choice, MBO, SPK